Construction of an ecological security pattern based on functional wetland theory: A case study in a landscape city - Zhang, Xiaoyu; Liu, Gong; Zheng, Zhi (Frontiers in Environmental Science, 2022)
Abstract: The high-intensity development of a city encroaches ecological land, such as lakes, rivers, and forests, which changes the stable land relationship, resulting in ecological security problems, such as regional waterlogging and decline of biodiversity. Identifying urban ecological system and constructing ecological security pattern (ESP) are of great importance for urban ecological protection and spatial planning. The complexity of ecological environment in landscape cities makes them more difficult for planning and construction than plain cities. Additionally, they are more susceptible to torrential rains, mountain torrents, and river tides in the process of urbanization. This study introduced functional wetland theory into the construction of ESP and obtained a new set of methods for landscape cities. Based on the functional wetland theory, "patch-corridor-matrix" model was used to combine geographic information system (GIS) runoff and catchment analysis with MSPA¬–MCR ecological corridor construction method to form a new wetland and habitat network by coupling the two together. Additionally, construction principles of protection priority, maximization of ecological benefits, guarantee of connectivity, and targeted design to guide the construction of landscape cities were put forward. This study takes the central urban area of Fuzhou as an example to show the application path of this method.